Ninjinyoeito Improves Behavioral Abnormalities and Hippocampal Neurogenesis in the Corticosterone Model of Depression - Murata, Kenta; Fujita, Nina; Takahashi, Ryuji; Inui, Akio (Frontiers in Pharmacology, 2018)
Ninjinyoeito (NYT), a traditional Chinese medicine consisting of 12 herbs, is designed to improve fatigue, cold limbs, anorexia, night sweats, and anemia. Recently, NYT was reported to improve cognitive outcome and depression in patients with Alzheimer’s disease. However, little is known about how NYT alleviates depression and cognitive dysfunction. In this study, we investigated the effects and mechanisms of NYT in a corticosterone (CORT)-induced model of depression. Chronic NYT treatment ameliorated the depressive-like behaviors induced by CORT treatment in three types of behavioral tests. In addition, chronic NYT treatment also improved memory disruptions induced by CORT in both the Y-maze and novel object recognition tests, without affecting locomotor activity. Furthermore, we also showed that NYT treatment attenuated the CORT-induced reduction in cell proliferation and immature neuronal cell numbers in mouse hippocampal dentate gyrus. These results suggest that NYT has therapeutic effects on CORT-induced behavioral abnormalities and inhibition of hippocampal neurogenesis.